Qualitative analysis of mothers' decision-making about vaccines for infants: the importance of trust - Benin, Andrea L; Wisler-Scher, Daryl J; Colson, Eve; Shapiro, Eugene D; Holmboe, Eric S (Pediatrics (Evanston), 2006)
The high visibility of controversies regarding vaccination makes it increasingly important to understand how parents decide whether to vaccinate their infants. The purpose of this research was to investigate decision-making about vaccinations for infants. We conducted qualitative, open-ended interviews. Subjects included mothers 1 to 3 days postpartum and again at 3 to 6 months. We addressed 3 topics: attitudes to vaccination, knowledge about vaccination, and decision-making. Mothers who intended to have their infants vaccinated ("vaccinators," n = 25) either agreed with or did not question vaccination or they accepted vaccination but had significant concerns. Mothers who did not intend to vaccinate ("nonvaccinators," n = 8) either completely rejected vaccination or they purposely delayed vaccinating/chose only some vaccines. Knowledge about which vaccines are recommended for children was poor among both vaccinators and nonvaccinators. The theme of trust in the medical profession was the central concept that underpinned all of the themes about decision-making. Promoters of vaccination included trusting the pediatrician, feeling satisfied by the pediatrician's discussion about vaccines, not wanting to diverge from the cultural norm, and wanting to adhere to the social contact. Inhibitors included feeling alienated by or unable to trust the pediatrician, having a trusting relationship with an influential homeopath/naturopath or other person who did not believe in vaccinating, worry about permanent side effects, beliefs that vaccine-preventable diseases are not serious, and feeling that since other children are vaccinated their child is not at risk. Trust or lack of trust and a relationship with a pediatrician or another influential person were pivotal for decision-making of new mothers about vaccinating their children. Attempts to work with mothers who are concerned about vaccinating their infants should focus not only on providing facts about vaccines but also on developing trusting and positive relationships.